Adaptive Community Policing and Public Security Transformation in Sat Samapta Through Technology-Based Patrol Systems and Participatory Governance - Wahyuning Tyas Utami (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Community policing has emerged as one of the most strategic approaches in strengthening democratic law enforcement, public security governance, and institutional legitimacy within modern societies. In Indonesia, Sat Samapta functions as the frontline preventive policing unit responsible for patrol activities, public order maintenance, community protection, crime prevention, and rapid security response. However, rapid technological advancement, urbanization, social conflict, digital crime expansion, public distrust, and transnational security threats have significantly transformed the operational environment of policing institutions. Conventional patrol systems are increasingly insufficient in addressing complex public security challenges requiring adaptive, collaborative, and technology-driven policing strategies. This study aims to analyze adaptive community policing and public security transformation in Sat Samapta through technology-based patrol systems and participatory governance mechanisms. The study employs a systematic literature review method by examining peer-reviewed international and national journal articles published between 2015 and 2026. The analysis integrates thematic analysis, comparative analysis, and narrative synthesis to identify governance patterns, institutional challenges, strategic innovations, and operational implications regarding adaptive policing transformation.